Tujuan Kemanfaatan Hukum Merancang Pedoman Sanksi Kekerasan Seksual di Perguruan Tinggi - Yulia Kurniaty; Rusli Muhammad; Aroma Elmina Martha (Jurnal Hukum IUS QUIA IUSTUM, 2024)
This research aims to examine the need to design the guidelines for sanctioning system in sexual violence in higher education institutions and the legal benefits that can be generated from it. The focus of this research departs from the results of a literature review regarding various strategies for handling cases of sexual violence in higher education institutions which are insufficient to cease the violence from occurring. The research method used is a library study of articles discussing sexual violence in higher education institutions, legal books discussing criminal guidelines, disparities, criminal law policies, utilitarianism philosophy, Law No. 12 of 2022 and Minister of Education and Culture Regulation No. 30 of 2022. The collected data were analyzed by using the qualitative descriptive techniques. The research results indicate that the goal derived from the legal benefits shall be achieved if the entire academic community feels safe and comfortable studying and working. This situation can only be realized if there is a guarantee of law enforcement for anyone who violates the primary rules in regards to committing sexual violence. In order to make it easier for stakeholders in higher education institutions who might have limited competence in the field of case advocacy, the said guidelines for sanctioning system can be used as a directive so that the sanctions imposed are useful in deterring the perpetrator, the victim's rights are restored and the good image of the university is maintained. Imposing sanctions on perpetrators of sexual violence in higher education institutions refers to six fundamental aspects of consideration, namely the error aspect, the impact aspect, the victim's loss aspect, the profit obtained by the perpetrator aspect, the aggravating and mitigating circumstances for the perpetrator, as well as determining the range of sanctions imposed.Keywords: Guidelines For Sanctioning System, Legal Benefits, Sexual Violence. AbstrakTujuan penelitian ini adalah untuk menelaah kemanfaatan hukum perlunya merancang pedoman sanksi kekerasan seksual di Perguruan Tinggi. Fokus penelitian ini berangkat dari hasil telaah pustaka atas beragam strategi penanganan kasus kekerasan seksual di perguruan tinggi tidak cukup mampu menghentikan terjadinya kekerasan ini. Metode penelitian yang digunakan adalah studi pustaka artikel-artikel yang membahas kekerasan seksual di Perguruan Tinggi, buku-buku ilmu hukum yang membahas pedoman pemidanaan, disparitas, kebijakan hukum pidana, filsafat aliran utilitarianisme, UU No.12 Tahun 2022 dan Permendikbudristek No.30 Tahun 2021. Data yang telah terkumpul dianalisis dengan teknik deskriptif kualitatif. Hasil penelitian menunjukkan bahwa tujuan kemanfaatan hukum tercapai jika seluruh sivitas akademika merasa aman dan nyaman belajar dan bekerja. Kondisi ini hanya dapat terwujud jika ada jaminan penegakkan hukum bagi setiap orang yang melanggar aturan utamanya melakukan kekerasan seksual. Demi memudahkan pemangku kepentingan Perguruan Tinggi yang memiliki ketebatasan kompetensi di bidang advokasi perkara, maka pedoman sanksi ini dapat digunakan sebagai panduan sehingga sanksi yang dijatuhkan bermanfaat membuat pelaku jera, hak korban dipulihkan dan nama baik perguruan tinggi tetap terjaga. Pejatuhan sanksi terhadap pelaku kekerasan seksual di perguruan tinggi mengacu pada enam aspek dasar pertimbangan yaitu aspek kesalahan, aspek dampak, aspek kerugian korban, aspek keuntungan yang diperoleh pelaku, aspek keadaan yang memberatkan dan meringan bagi pelaku, dan penentuan rentang penjatuhan sanksi.Kata kunci: Kekerasan Seksual, Kemanfaatan Hukum, Pedoman Sanksi.